2005
DOI: 10.1111/j.1365-2934.2005.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership: a cascading chain reaction

Abstract: Historical influences still permeate contemporary nursing practise. These are mirrored in organizational philosophies, transactional and autocratic leadership styles and disempowered staff. Whilst there is disparity amongst the theorists' definitions of leadership, there is consensus pertaining to the attributes necessary to realize effective leadership. Transformational leadership is heralded as new criterion for nurse managers, and can be achieved through training, education and professional development in k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 40 publications
7
101
0
3
Order By: Relevance
“…We believe this has strengthened our results. It has been suggested that transformational leadership play a vital role in healthcare (Sofarelli and Brown, 1998;Thyer 2003;Murphy, 2005) particularly as stress and depression are reported to be highly prevalent in healthcare occupations (Wieclaw et al, 2005). Large numbers of studies on transformational leadership are therefore conducted in healthcare settings, and our findings contribute to this literature.…”
Section: Resultssupporting
confidence: 69%
“…We believe this has strengthened our results. It has been suggested that transformational leadership play a vital role in healthcare (Sofarelli and Brown, 1998;Thyer 2003;Murphy, 2005) particularly as stress and depression are reported to be highly prevalent in healthcare occupations (Wieclaw et al, 2005). Large numbers of studies on transformational leadership are therefore conducted in healthcare settings, and our findings contribute to this literature.…”
Section: Resultssupporting
confidence: 69%
“…A number of these studies have concluded that health care leadership runs under transactional style (Thyer, 2003;Murphy, 2005). Some Mwenje and Mwenje 29 observations suggest that both transactional and autocratic styles predominate (Murphy 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One sector in which leadership styles, especially that of transformational and transactional styles have been discussed, is nursing management (Thyer, 2003;Murphy, 2005;Chen et al, 2005). A number of these studies have concluded that health care leadership runs under transactional style (Thyer, 2003;Murphy, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations